Self-Efficacy as a Psychological Mechanism in Sufi Healing: A Qualitative Study in an Islamic Boarding School - Zaen Musyrifin; Aziz Muslim (DAWUH : Islamic Communication Journal, 2026)
Spiritual healing has increasingly been recognized as a meaningful resource in mental health recovery; however, the psychological mechanisms through which spiritual practices facilitate recovery remain insufficiently examined, particularly within Islamic healing traditions. Drawing on Bandura’s social cognitive theory, this study investigates self-efficacy as a central psychological mechanism in Sufi healing and explores how structured spiritual practices contribute to strengthening individuals’ perceived capacity to cope with psychological distress. Using a qualitative phenomenological design, this study was conducted at an Islamic boarding school in Indonesia that integrates Sufi-based spiritual healing practices. Data were collected through in-depth semi-structured interviews with ten participants, including spiritual leaders, mentors, and individuals undergoing spiritual healing, and analyzed using thematic analysis. Four interrelated themes emerged: restored confidence, spiritual empowerment, psychological strengthening, and renewed sense of agency. Participants described increased emotional stability, enhanced confidence, and greater perceived control over their lives following engagement in spiritual practices such as dhikr, prayer, and guided mentorship. The findings suggest that Sufi healing facilitates psychological recovery not solely through spiritual experience but through strengthening self-efficacy beliefs that support adaptive coping and resilience. This study advances the field of spirituality and mental health by empirically positioning self-efficacy as a mediating psychological mechanism linking spiritual practice and psychological recovery within a non-Western Islamic context.